Knowledge Organization and Management in the Domain of Environment and Earth Observation (KOMEEO) (Nomos, 2022)
The volume contains the proceedings of the KOMEEO (Knowledge Organization and Management in the domain of Environment and Earth Observation) international conference, organized in the field of the European ERA-PLANET (The European Network for observing our changing Planet) H2020 program. Papers present research projects and experiences related to different aspects of organizing knowledge in the environmental domain, which nowadays is receiving great attention from the European Union. In particular, they address topics related to Knowledge Organization Systems (KOSs), to their application in specific contexts, to the extraction of metadata, to the achievement of semantic interoperability. With contributions by Richard Absalom, Prof. Stefano Allegrezza, Dr. Giovanna Aracri, Armando Bartucci, Dr. Assunta Caruso, Prof. Eugenio Casario, Dr. Maria Teresa Chiaravalloti, Sergio Cinnirella, Martin Critelli, Sabina Di Franco, Prof. Antonietta Folino, Dr. Claudia Lanza, Francesca M.C. Messiniti, Prof. Alexander Murzaku, Dr. Anna Perri, Dr. Erika Pasceri, Paolo Plini, Prof. Anna Rovella and Rosamaria Salvatori.